1963
DOI: 10.1161/01.res.12.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Myocardium in Cardiomegaly

Abstract: The adult rat's ventricular myocardium is able to increase its mass markedly while maintaining its unit quality. It does so by maintaining constant the design of the sarcomeres: an increase in length is accomplished by the addition of sarcomeres in series; an increase in tension production is accomplished by the addition of more cross-sectional area of a uniform quality. This was shown by the almost constant concentration of the contractile protein, actomyosin, as well as by the histologic evidence of the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
1

Year Published

1968
1968
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(27 citation statements)
references
References 19 publications
3
23
1
Order By: Relevance
“…Ventricular volumes were not determined, and therefore, these variables cannot be accurately quantitated. However, it has been reported that passive length-tension curves of myocardium from rats that had been chronically swum are normal (4,24). This suggests that at the same atrial pressure the diastolic volume of CH and SH would be the same.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular volumes were not determined, and therefore, these variables cannot be accurately quantitated. However, it has been reported that passive length-tension curves of myocardium from rats that had been chronically swum are normal (4,24). This suggests that at the same atrial pressure the diastolic volume of CH and SH would be the same.…”
Section: Discussionmentioning
confidence: 99%
“…Although earlier studies reported that contractile function of hypertrophied myocardium was normal or even "supernormal" (1)(2)(3)(4), the methods used to assess contractile state and the manner in which this function was corrected for differences in muscle mass have been criticized. More recently, Spann, Received for publication 10 May 1974 and in revised form 16 August 1974.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence to support this impression has been gained primarily from the observation that patients dying with COPD often have left ventricular hypertrophy at postmortem examination (2)(3)(4)(5)(6)(7), and the possible mechanisms for this have been summarized (7). However, the presence of myocardial hypertrophy does not necessarily indicate depressed myocardial function since it has been demonstrated that the hypertrophied myocardium can function normally (8) or even supernormally (9)(10)(11)(12)(13). Furthermore, definitive conclusions concerning left ventricular function in these patients cannot be made from the vast amount of hemodynamic data accumulated from cardiac catheterization studied which have been summarized recently (14).…”
Section: Introductionmentioning
confidence: 99%